EMPLOYEE PSYCHOLOGICAL ANALYSIS: Communication, Self Esteem, and Self Efficacy - Gozali, Ahmad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Behind the achievements and goals achieved, there are many sacrifices, ranging from emotional, physical, to mental. This situation is an abstract factor that becomes a motor for a worker in achieving good work results. This confirms, behind the achievement of the company's interests, there is a great effort from a worker, which sacrifices his emotionality. This study seeks to reveal information about the psychological factors of employees in achieving performance. The method used in this study is a derivative of the quantitative approach, namely the survey method. While the operational research method, using associative techniques with statistical regression analysis as proving the probability. The research subjects were employees of PT Aerofood Acs Indonesia with a purposive sampling technique, a total of 100 people. Data collection is done primarily through the distribution of questionnaires, either directly or using google forms. In measuring the research instrument, the Likert scale was used. The results of the study explain that psychological factors have a very real contribution in achieving good work results. It is undeniable, feeling happy or comfortable can encourage the birth of measurable and maximum work behavior. So often, because of this feeling of pleasure/happiness, employees work more than the standards that have been set. On the other hand, if the psychological aspect is disturbed, then there is a tendency to decrease work performance and productivity.